Personal protective equipment and health-care workers - Anitta Jose Ellenkil; Nitin Dutt Bharadwajj; Uday Bhakar Mishra (Wolters Kluwer -Medknow Publications, 2024)
Background and Objective: The study was carried out to assess the knowledge, attitude, and practice viz-a-viz to the use of Personnel protective equipment among the health-care staff of a government tertiary care teaching hospital. Methodology: The study was performed in a government tertiary care teaching hospital. The study design was cross-sectional and descriptive. The study was carried out in the Clinical areas of the hospital and included 407 health-care professionals (academic resident doctors, nursing officers, paramedical staff and housekeeping staff) who have consented to participate in the study. A structured and validated questionnaire was prepared based on the standard guidelines described in the Infection Prevention and Control Manual, MOHFW, GOI published in 2018. The parts of the study tool were divided into five parts. The results were statistically analyzed (MS Office spreadsheet version 2007 and IBM-SPSS Version 20). Results: The study included 407 participants; 91 (22.4%) academic resident doctors, 122 (30%) nursing officers, 23 (5.7%) paramedical staff, and 171 (42%) housekeeping staff, respectively. The overall knowledge, attitude, and practice aspect of the personal protective equipment (PPE) were comparatively low. The overall mean score of knowledge, attitude, and practice regarding PPE was 0.73, 0.72, and 0.22 out of 1. Conclusion and Recommendations: The knowledge aspect of PPE of health-care professionals was good for nursing officers whereas with respect to the attitude and practice aspect, it was found that in the majority of areas, the housekeeping staff were performing better than the other cadres. The author recommends regular inspection by the clinicians and administrators to ensure compliance; and to provide training for the health-care professionals with regard to the types of PPE to be used and when all to be used as per the job undertaken as a reminder/continuous medical education.